2022
DOI: 10.1155/2022/7303647
|View full text |Cite
|
Sign up to set email alerts
|

Multislice Spiral Computer Tomography Findings of Simple Congenital Middle Ear Malformations

Abstract: Background. Simple congenital middle ear malformations (SCMEMs) are a group of congenital ear malformations. The study aims to analyze the multi-slice spiral computer tomography (MSCT) manifestations of normal ears and SCMEM ears. Objectives. This study aimed to investigate the MSCT manifestations of normal ears and SCMEM ears and to evaluate the relationship between the SCMEM and the tympanic segment of the FNC pathway. Methods. This was a retrospective case-control study. Patients who were diagnosed with SCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…Kang et al demonstrated its widespread application by establishing the clinical significance of coronal MSCT multi-planar reconstruction in detecting a downward and inward shift of the tympanic segment of the FN covering the oval window in patients with simple middle ear malformations. 29 In terms of surgical complications, the finding that no FN injury occurred is consistent with what is reported in the literature, with an overall postoperative FN weakness of 0.8%. 30 Among other adverse events encountered in our series, 2 gushers out of 165 patients (1.2%) have been the ones of most concern.…”
Section: Discussionsupporting
confidence: 89%
“…Kang et al demonstrated its widespread application by establishing the clinical significance of coronal MSCT multi-planar reconstruction in detecting a downward and inward shift of the tympanic segment of the FN covering the oval window in patients with simple middle ear malformations. 29 In terms of surgical complications, the finding that no FN injury occurred is consistent with what is reported in the literature, with an overall postoperative FN weakness of 0.8%. 30 Among other adverse events encountered in our series, 2 gushers out of 165 patients (1.2%) have been the ones of most concern.…”
Section: Discussionsupporting
confidence: 89%